1995
DOI: 10.1063/1.1145562
|View full text |Cite
|
Sign up to set email alerts
|

Trace gas detection with cavity ring down spectroscopy

Abstract: Depth-resolved cathodoluminescence spectroscopy of silicon supersaturated with sulfur Appl. Phys. Lett. 102, 031909 (2013) Effect of plasma N2 and thermal NH3 nitridation in HfO2 for ultrathin equivalent oxide thickness J. Appl. Phys. 113, 044103 (2013) Atomic-scale characterization of germanium isotopic multilayers by atom probe tomography J. Appl. Phys. 113, 026101 (2013) Monitoring metal contamination of silicon by multiwavelength room temperature photoluminescence spectroscopy AIP Advances 2, 0421… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
124
0
3

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(129 citation statements)
references
References 15 publications
2
124
0
3
Order By: Relevance
“…Jongma et al (1995) pioneered ultraviolet CRDS detection of trace gases including Hg 0 with a frequency-doubled, pulsed dye laser (linewidth of 0.1 cm −1 ) pumped by a frequency-tripled Nd:YAG laser at 355 nm and a 0.45 m length open-path CRDS cavity using mirrors with 99.6% reflectivity. This setup was used to measure Hg 0 background concentrations (i.e., 63 ng m −3 ) in their laboratory with a noise-equivalent (1σ detection limit of 9 ng m −3 for 3 s averaging time.…”
Section: Performance Of Previous Cavity Ring-down Spectrometers For Hmentioning
confidence: 99%
“…Jongma et al (1995) pioneered ultraviolet CRDS detection of trace gases including Hg 0 with a frequency-doubled, pulsed dye laser (linewidth of 0.1 cm −1 ) pumped by a frequency-tripled Nd:YAG laser at 355 nm and a 0.45 m length open-path CRDS cavity using mirrors with 99.6% reflectivity. This setup was used to measure Hg 0 background concentrations (i.e., 63 ng m −3 ) in their laboratory with a noise-equivalent (1σ detection limit of 9 ng m −3 for 3 s averaging time.…”
Section: Performance Of Previous Cavity Ring-down Spectrometers For Hmentioning
confidence: 99%
“…9,14,15 With the cavity designed as described above, the cavity mode spectrum is quasicontinuous 16 due to the lifting of the degeneracy of the longitudinal and transverse modes. As long as the laser linewidth is spectrally narrower than the absorption feature of the species under study, the time dependence of the light intensity inside the cavity is correctly described with a single exponentially decaying curve.…”
Section: Crd Detection Of Dpamentioning
confidence: 99%
“…As long as the laser linewidth is spectrally narrower than the absorption feature of the species under study, the time dependence of the light intensity inside the cavity is correctly described with a single exponentially decaying curve. 15,17 It is noted once more, that in a CRD experiment the rate of absorption of a light pulse confined in a closed optical cavity is measured and the measurement is therefore independent of light source intensity fluctuations, as long as the spectral intensity distribution of the light stays constant from pulse to pulse. The ring down transient is displayed on the same digital oscilloscope, and averaged over typically 25 laser pulses.…”
Section: Crd Detection Of Dpamentioning
confidence: 99%
“…5 As long as mirrors with a sufficiently high reflectivity, detectors with a sufficiently fast time response, and tunable ͑pulsed͒ light sources are available there is no intrinsic limitation to the spectral region in which CRD can be applied. By now, successful application of CRD spectroscopy has been demonstrated from the uv part of the spectrum 6 to the ir spectral region. 7,8 The application of CRD is most straightforward if it can be assumed that the linewidth of the light source can be neglected relative to the width of the molecular absorption.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown, however, that if this assumption is no longer valid, one can still extract the correct absorption coefficient from the measured transients, provided the spectral intensity distribution of the light source is known. 6,9 As a consequence, it has been experimentally demonstrated that one does not necessarily need a narrow-band pulsed laser to perform a CRD experiment. One might just as well use a polychromatic light source and extract the spectral information after spectrally dispersing the light exiting the cavity, either in a monochromator or by using a Fourier transform spectrometer.…”
Section: Introductionmentioning
confidence: 99%